Synthesis of S-Linked N-Acetylneuraminic Acid Derivatives via Photoinduced Thiol–ene and Thiol–yne Couplings - Csávás, Magdolna; Herczeg, Mihály; Borbás, Anikó (Synlett, 2013)
Thio-linked mono- and bivalent mimetics of α(2→3) and α(2→6)-linked sialosides were prepared by photoinduced hydrothiolation of alkenes and alkynes with the 2-mercapto sialic acid. Thiosialylation of 6-O-allyl- or 3-O-allyl-substituted galactose derivatives has been carried out by the thiol–ene click reaction. Double thiosialylation has also been achieved via thiol–yne chemistry using propargylated galactose derivatives as the alkyne components and the peracetylated 2-mercapto sialic acid as the thiol.
Keywords: carbohydrates; N-acetylneuraminic acid; radical additions; thiol–ene/thiol–yne coupling; thiosialosides